The quest for efficiency through outsourcing services - Braz, Erivelton Toreta; Patrocinio Gomes, Vanielle Aparecida; Tosta, Marielce de Cássia Ribeiro; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2020)
The outsourcing of services is a subject discussed worldwide due to its possible advantages, among them cost reduction stands out, however there are elements that make this system more complex and less deterministic. Objective: to show an overview on the topic of outsourcing services at the national and international level, as well as the opportunities, areas and research to be explored in these categories. Method: The present study presents a systematic analysis of the theme in the scientific community using the 10 most cited articles in the Scielo and Web of Science databases as a cross-section of their realities and from there point out gaps to be explored. Results: From the qualitative analysis of the 20 articles, it was possible to determine and position Brazil's contribution to the theme in relation to the world; the most used expressions; the evolution of the most outstanding publications, authors, organizations and countries, as well as the gaps found in the sample. Final considerations: The outsourcing of services is a topic little discussed in the country but with a large framework of discussions at an international level, however there are still contradictions about the topic such as the managerial view about the productive model of cost reduction and the social view that discusses the consequences of outsourcing on the precariousness of labor relations and workers' health.